Larger and structurally complex woodland creation sites provide greater benefits for woodland plants - Emily H. Waddell; Elisa Fuentes‐Montemayor; Kirsty J. Park; Peter Carey; Matt Guy; Nicholas A. Macgregor; Kevin Watts (Ecological Solutions and Evidence, 2024)
Abstract Reforestation initiatives are underway across the world. However, we know relatively little about the ecological consequences of creating and restoring forest ecosystems, and there is a lack of studies examining the drivers of species colonisation and establishment across appropriate temporal and spatial scales to inform conservation practice. Using data from a long‐term natural experiment (the WrEN project), we explore ground plant species occurrence and community composition in 102 woodland creation sites (10–160 years since planting), and 27 old growth woodlands (>250 years). We conducted field surveys to collect data on occurrence of plant species (classified into woodland specialist, woodland generalist, or non‐woodland) and used Structural Equation Modelling to investigate the influence of local (age, size, woodland structure) and landscape‐level (amount of surrounding woodland) attributes on species richness. Woodland generalists are readily colonising woodland creation sites to similar levels found in old growth woodlands. However, there were fewer woodland specialist and more non‐woodland plants in creation sites than in old growth. Specialists and generalists were more likely to be present in larger woodlands and those with higher variation in tree size (which was higher in older woodlands) and did not appear to be influenced by features of the surrounding landscape. Some plant communities in older creation sites (80–160 years) were similar to old growth, suggesting colonisation of a typical old growth flora over time; however, some sites were shifting away from this trajectory. Specialists are slow to colonise woodland creation sites and their occurrence was low relative to old growth woodlands even after >80 years. However, woodland management to increase structural complexity may enhance the establishment of woodland plants. The lack of influence of the surrounding landscape on species occurrence is likely due to most of the study sites being relatively isolated resulting in limited colonisation. This suggests that new woodlands need to be adjacent or very near to existing woodland to receive the benefits of increased colonisation. Our results highlight the importance of creating large and structurally complex woodlands, close to existing woodlands to facilitate the colonisation and establishment of woodland plants.